FRAMING PEMBERITAAN PRABOWO DALAM MEMBENTUK CITRA POSITIF PADA MEDIA TV ONE - Ardinata, Suci Ria; Marini (Komsospol, 2022)
Political reporting in the mass media has an important role in shaping people’s views of political leaders and public figures. Self-image is very important in people’s perceptions of their leaders. One news channel that has a big influence is TV One. How TV One frames the news about Prabowo’s candidacy can have a significant impact on the public’s image and perception of him. This research is a type of analytical research using a qualitative approach. The data used in this research comes from books or articles about news framing, as well as news from TV One which depicts Prabowo in a positive way. The data in this research was obtained from TV One. The data collection method applied is by searching for news on the TV One news portal, which will then be analyzed. This research aims to analyze how Prabowo Subianto’s news is framed in forming his positive image through mass media, especially TV ONE. Framing in this context refers to highlighting and presenting news with a specific purpose. It is hoped that the results of this research will provide an in-depth understanding of how TV ONE, as a mass media, uses framing in its reporting to form a positive image of Prabowo Subianto